Unemployment and expenditure on health and education as mediators of the association between toothbrushing and global income inequalities - Maha El Tantawi; Nourhan M. Aly; Morenike Oluwatoyin Folayan (BMC, 2022)
Abstract Objective The study assessed the association of country-level income inequalities with the percentage of schoolchildren toothbrushing-at-least-twice-daily; and the mediating effect of country-level unemployment rate and governmental expenditure on health and education (EH&E). Methods This was an ecological study. The dependent variable was country-level toothbrushing-at-least-twice-daily among 11-15-year-old schoolchildren. Data for the period 2009 to 2019 were extracted from two global surveys about schoolchildren's health and from manuscripts identified through a systematic search of three databases. The independent variable was country-level income inequalities measured by the Gini coefficient (GC) extracted from the Sustainable Development Report 2021. The mediators were the unemployment rate and EH&E. We stratified the sample by the level of GC and assessed the correlation between the dependent and independent variables in each stratum. Linear regression was used to assess the relations between the dependent and independent variables, and mediation path analysis was used to quantify the direct, indirect, and total effects. Results Data were available for 127 countries. The mean (SD) percentage of children who brushed-at-least-twice-daily was 67.3 (16.1), the mean (SD) GC = 41.4 (8.2), unemployment rate = 7.5 (4.7) and EH&E = 8.4 (3.3). The percentage of children brushing at-least-twice-daily had weak and non-significant correlation with GC that was positive in countries with the least inequality and negative for countries with higher levels of inequality. A greater percentage of schoolchildren brushing-at-least-twice-daily was significantly associated with higher GC (B = 0.76, 95%CI: 0.33, 1.18), greater EH&E (B = 1.67, 95%CI: 0.69, 2.64) and lower unemployment rate (B=-1.03, 95%CI: -1.71, -0.35). GC had a significant direct positive effect (B = 0.76, 95%CI: 0.33, 1.18), a significant indirect negative effect through unemployment and EH&E (B=-0.47, 95%CI: -0.79, -0.24) and a non-significant total positive effect (B = 0.29, 95%CI: -0.09, 0.67) on the percentage of schoolchildren brushing-at-least-twice-daily. Conclusion Unemployment and EH&E mediated the association between income inequality and toothbrushing. Country-level factors may indirectly impact toothbrushing.